1999
DOI: 10.1111/j.1540-8159.1999.tb00606.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Ventricular Function During High Right Ventricular Septal and Apical Pacing after His‐Bundle Ablation for Refractory Atrial Fibrillation

Abstract: This study compares LV performance during high right ventricular septal (RVS) and apical (RVA) pacing in patients with LV dysfunction who underwent His-bundle ablation for chronic AF. We inserted a passive fixation pacing electrode into the RVA and an active fixation electrode in the RVS. A dual chamber, rate responsive pulse generator stimulated the RVA through the ventricular port and the RVS via the atrial port. Patients were randomized to initial RVA (VVIR) or RVS (AAIR) pacing for 2 months. The pacing sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
128
0
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(136 citation statements)
references
References 11 publications
1
128
0
7
Order By: Relevance
“…2 However, hemodynamic deterioration in relation to worsening mitral regurgitation (MR) can occur in a small number of patients following AVN ablation and pacing therapy 5,6 and those with moderate MR prior to the ablation seem prone to this complication. 5,7 High right ventricular (RV) septal pacing produces shorter QRS duration and better chronic LV function than RV apical pacing in patients with mild to moderate LV dysfunction and chronic atrial fibrillation after AVN ablation, [8][9][10][11] but direct His-bundle pacing produces a more physiological ventricular contraction and may result in less worsening of MR in comparison. 12,13 We describe a case of successful permanent His-bundle pacing after AVN ablation in a patient with chronic atrial fibrillation and MR.…”
mentioning
confidence: 99%
“…2 However, hemodynamic deterioration in relation to worsening mitral regurgitation (MR) can occur in a small number of patients following AVN ablation and pacing therapy 5,6 and those with moderate MR prior to the ablation seem prone to this complication. 5,7 High right ventricular (RV) septal pacing produces shorter QRS duration and better chronic LV function than RV apical pacing in patients with mild to moderate LV dysfunction and chronic atrial fibrillation after AVN ablation, [8][9][10][11] but direct His-bundle pacing produces a more physiological ventricular contraction and may result in less worsening of MR in comparison. 12,13 We describe a case of successful permanent His-bundle pacing after AVN ablation in a patient with chronic atrial fibrillation and MR.…”
mentioning
confidence: 99%
“…Pacing on the right ventricular (RV) septum, at high (septal RVOT pacing) (Giudici et al, 1997;Kolettis et al, 2000;Bourke et al, 2002;Tse et al, 2002;Dabrowska-Kugacka et al, 2009;Gong et al, 2009;Leong et al, 2010;Yoshikawa et al, 2010), mid (Yu et al, 2007;Cano et al, 2010;Muto et al, 2007) or lower (Flevari et al, 2009) septal pacing position has been introduced as a potentially favorable alternative to RVA pacing to preserve a more physiologic ventricular activation. Previous investigations of alternative pacing sites have yielded inconsistent results (Mera et al, 1999;Giudici et al, 1997;Bourke et al, 2002;Victor et al, 2006;Kypta et al, 2008;Dabrowska-Kugacka et al, 2009;Tse et al Europace 2009;Victor et al, 1999) which may be attributable, in part, to the fact that the pacing site was determined on a topological rather than functional basis (Giudici & Karpawich, 1999). Many previous studies (Schwaab et al, 1999;Victor et al, 2006;Yu et al, 2007;Ng et al, 2009;Takemoto et al, 2009;Tse et al, Europace 2009, Gong et al, 2009Leong et al, 2010;Schwaab et al, 2001), have showed that septal pacing induced shorter paced QRS duration than RVA pacing did.…”
Section: Electric and Mechanic LV Synchronymentioning
confidence: 92%
“…However, electrocardiographic criteria such as negative deflection of lead I and positive initial R-waves of the paced ventricular complex in leads II and III ( Schwaab et al, 2001;McGavigan et al,2006;Lieberman et al, 2004;Balt et al, 2010) or the narrowest paced QRS complex available during the mapping of the interventricular septum (Tse et al, 2002;Tse et al, 2009a;Tse et al, 2009b;Schwaab et al, 2001), were not used uniformly. Tse et al and Mera et al (Mera et al, 1999) have postulated that the paced QRS duration is a practical indicator for determining the optimal RV pacing site. However, Schwab et al (Schwaab et al, 2001) have found the detailed mapping of the RV with precise measurements of QRS duration has been found to be impractical.…”
Section: Rv Septal Pacing 321 Technical Aspect Of Lead Implantationmentioning
confidence: 99%
See 1 more Smart Citation
“…След-ствием апикальной стимуляции является запоз-далое сокращение папиллярных мышц ПЖ с формированием ТР [39]. Выбор альтернатив-ной области стимуляции, например области выводного тракта ПЖ, согласно данным ряда авторов [28,[46][47], является одним из приори-тетов. Эксперты считают, что при апикально имплантированных электродах существует больший риск повреждения аппарата ТК, осо-бенно задней створки, в сравнении с электрода-ми, фиксированными в области выводного тракта ПЖ.…”
Section: кардиостимуляцияunclassified